Chemical and microbiological insights into two littoral Antarctic demosponge species: Haliclona (Rhizoniera) dancoi (Topsent 1901) and Haliclona (Rhizoniera) scotti (Kirkpatrick 1907) - Papale, Maria; Giannarelli, Stefania; Azzaro di Rosamarina, Maurizio; Ghezzi, Lisa; Lo Giudice, Angelina; Rizzo, Carmen (Frontiers in Microbiology, 2024)
The Antarctic demosponge species Haliclona dancoi and Haliclona scotti were targeted for the determination of persistent organic pollutant (i.e., polychlorobiphenyls, PCBs, and polycyclic aromatic hydrocarbons, PAHs) and trace metal concentrations, along with the characterization of the associated prokaryotic communities by the 16S rRNA next generation sequencing, to evaluate possible relationships between pollutant accumulation (e.g., as a stress factor) and prokaryotic community composition in Antarctic sponges. To the best of our knowledge, this approach has been never applied before. Notably, both chemical and microbiological data on H. scotti (a quite rare species in the Ross Sea) are here reported for the first time, as well as the determination of PAHs in Antarctic Porifera. Both sponge species generally contained higher amounts of pollutants than the surrounding sediment and seawater, thus demonstrating their accumulation capability. The structure of the associated prokaryotic communities, even if differing at order and genus levels between the two sponge species, was dominated by Proteobacteria and Bacteroidota (with Archaea abundances that were negligible) and appeared in sharp contrast to communities inhabiting the bulk environment. Results suggested that some bacterial groups associated with H. dancoi and H. scotti were significantly (positively or negatively) correlated to the occurrence of certain contaminants.